Persepsi Perawat tentang Peran dalam Meningkatkan Keselamatan Pasien - Afeus Halawa; Setiawan Setiawan; Bustami Syam (Journal of Telenursing (JOTING), 2021)
This study explores the perceptions of nurses on the role in improving patient safety at the Deli Medan General Hospital. This research is qualitative research using the method of Focus Group Discussion (FGD). This study's results reveal four themes related to the nurse's perception of the role in carrying outpatients at the Deli Medan General Hospital. In conclusion, there are four themes of nurses' perceptions about the role in implementing patient safety, namely: 1) events that almost cause harm to patients; 2) role in improving patient safety; 3) supporting factors for the implementation of roles in improving patient safety; 4) factors inhibiting the implementation of the role in improving patient safety. Keywords: Patient Safety, Role, Nurse Perception